Additional growth of dominant follicle during synchronized ovulatory cycle affects ovulatory follicle size, corpus luteum parameters, and progesterone level in Northern Thai native cattle - Jakree Jitjumnong (2020)
© 2019, Thammasat University. All rights reserved. The aim of this research was to evaluate the additional growth rate of dominant follicle (DF) using a pregnant mare’s serum gonadotropin (PMSG) in a 7-day progesterone (P4)-gonadotropin releasing hormone (GnRH)-based program on follicular development and luteal function in White Lamphun cows. Cows in the PMSG-treated group (n=10) received PMSG on day of a P4 device removal (on Day 7) in 7-day P4-GnRH-based program, while cows in the PMSG-untreated group (n=10) did not receive PMSG treatment. Ultrasonography was used to scan ovaries to determine development of ovulatory follicle (OF) and formation of corpus luteum (CL). Blood samples were collected to examine P4 concentration. The OF diameter and CL parameters (size, area, and volume) were greater in the PMSG-treated cows than in the PMSG-untreated cows (P < 0.05). Ten days after ovulation, the greatest P4 concentration was found in the PMSG-treated group (P < 0.05). In conclusion, additional growth rate of DF using PMSG in 7-day P4-GnRH-based program results in increase in OF development, CL parameters, and greater P4 concentration in White Lamphun cows.